Role of Interleukin-36 in Response to Pseudomonas Aeruginosa Infection - Muslim Idan Mohsin1 , Mohammed Jasim Al-Shamarti1 , Rusul Idan Mohsin3 , Sarmad Al-Sahaf2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: One of the causative agents of the lower respiratory tract (LRT) is Pseudomonas aeruginosa which can lead to severe infection associated with a lung infection. Many cytokines are secreted in response to bacterial infection, in particular, interleukin IL-36 cytokine in response to P. aeruginosa infection. IL36 promotes primary immune response via binding to the IL-36 receptor (IL-36R). Indeed, an over activity of IL-36 might be an initiating factor for many immunopathologic sceneries in pneumonia. The aims of Study: the involvement of IL-36 in the P. aeruginosa infection could be a clue to find a specific way for treatments of different inflammatory and degenerative lung diseases. Methodology and Results: we used manual and VITEK2 system to isolate and purify all the species, also using qPCR real-time to demonstrate that the involvement of IL-36 cytokine in response P. aeruginosa infection which is isolated from (LRT). We found that one of the most common pathogens is P. aeruginosa after Klebsiella pneumonia, and more resistance bacterium against antibiotics is P. aeruginosa (P4). Furthermore, we found that IL-36 cytokine increased in response to P. aeruginosa infection. Conclusion: P. aeruginosa is one of the main causative agents in LRT in many hospitals in Iraq, and the contamination and antibiotics resistance for these nosocomial pathogens is increased. Also, IL-36 expression significantly upregulated in human lung epithelial (A549 cells) after infected by P. aeruginosa at the mRNA level.